WEB-BASED E-ARCHIVES APPLICATION DESIGN INNOVATION TO FACILITATE SYSTEMATIC DOCUMENT STORAGE AND FACILITIES ARCHIVES DISCOVERY SPEED AT SMP NEGERI 38, MEDAN MARELAN DISTRICT - Qamariah, Inneke; Yuliaty, Tetty; Ibrahim Nainggolan, Pauzi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
The purpose of using electronic media is expected to be able to help archive managers so they can manage records easily and quickly. The use of information technology in office work can have an impact on increasing the number of electronic records managed. Through the management of electronic records, it is expected to improve the quality of archive services to all parties in need, including leaders in the context of decision making. The application of electronic media in archive management will have the advantage of being easy, fast and economical. Thus, a solution is needed to solve the problems faced by partners. The solution to solving this problem is to provide applications/software that can be used for storing digital archives,